Transforming in the visiting assistant professor role: collaborative self-study research in physical education teacher education. Issue 5 (13th June 2019) - Ressler, James D.; Richards, K. Andrew R.
ABSTRACT: Transitioning into faculty roles can be a challenging experience. Responsibilities related to teaching, research, and service can be difficult to balance, and mismatch between personal preferences for work focus and instructional expectations can be problematic. This is particularly true of visiting assistant professors who want to work toward tenure-track positions, but whose current job focus is on teaching. Through transformative learning theory and employing the methodologies of self-study, we sought to understand the experiences of Kevin, the second author and a first-year visiting assistant professor. We draw data from Kevin's reflective journal and discussions between Kevin and his critical friend, Jim. Themes included (a) becoming an academic, (b) a hard-wired disposition toward work, and (c) influence of the VAP on emotional and personal health. Results are discussed through the lens of transformative learning theory and focus on Kevin's growth during his year as a visiting assistant professor.